2006 27th IEEE International Real-Time Systems Symposium (RTSS'06) 2006
DOI: 10.1109/rtss.2006.12
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Derivation of Loop Bounds and Infeasible Paths for WCET Analysis Using Abstract Execution

Abstract: Static Worst-Case Execution Time (WCET) analysis is a technique to derive upper bounds for the execution times of programs. Such bounds are crucial when designing and verifying real-time systems. A key component for statically deriving safe and tight WCET bounds is information on the possible program flow through the program. Such flow information can be provided manually by user annotations, or automatically by a flow analysis. To make WCET analysis as simple and safe as possible, it should preferably be auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 11 publications
0
134
0
Order By: Relevance
“…We will also do the flow analysis on ALF, using SWEET's powerful flow analysis methods [23,24,25]. The result will be given as constraints on the number of times different basic blocks of the ALF code can be executed and edges of the control flow graph can be followed.…”
Section: Methodsmentioning
confidence: 99%
“…We will also do the flow analysis on ALF, using SWEET's powerful flow analysis methods [23,24,25]. The result will be given as constraints on the number of times different basic blocks of the ALF code can be executed and edges of the control flow graph can be followed.…”
Section: Methodsmentioning
confidence: 99%
“…This includes, for instance, loop and infeasible paths analyses [7,8], cache analysis [9], and path enumeration techniques [10]. There exist several commercial tools, such as aiT 2 and Bound-T 3 , as well as academic implementations, such as SWEET 4 from Mälardalen University.…”
Section: Related Workmentioning
confidence: 99%
“…Although there exists a large body of work in the area of WCET analysis [7,8,9,10,11], surprisingly little has been done with interactive timing analsysis. Previous work addresses fast WCET analysis [12], interactive C code analysis [13], analysis of Java code [14] and timing analysis of Matlab/Simulink models [15].…”
Section: Introductionmentioning
confidence: 99%
“…taskss possible execution flows, i.e., different execution paths in the code cause certain variations of executions for a typical task. Variations in the execution of a task can happen in terms of different input data, and software characteristics such as loop iterations, nested loops, infeasible paths, execution frequencies of code parts, etc [15,11,28]. As a general model of this behavior, it can be observed that the critical sections of tasks may happen at different times within the task execution.…”
Section: Algorithm Descriptionmentioning
confidence: 99%